Upaya Peningkatan Kreativitas Anak Melalui Kegiatan Menggambar Bebas di TK PAUD Harapan Bunda Sungai Talang - Putri Yeni; Endang Citrowati (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
The application of free drawing to improve children's creativity in Harapan Bunda Sungai Talang PAUD Kindergarten is very beneficial for children and teachers because it can improve children's creativity, improving children's creativity in Harapan Bunda Sungai Talang PAUD Kindergarten shows good and satisfying results, this is evident from the total number of children who participated in the free drawing activity, which was 100% (14 children) and through free drawing activities it can be seen that children have good creativity skills, and can be seen from the way children use tools and the way children express their imagination in these activities. In addition, children have a great curiosity, have a sense of beauty, and children are free to express their opinions in free drawing activities.